Preservation of a Rare Art, Okokan, through the Quality Improvement in Musical Instrument Quality and Merchandise Design - Swandi, I Wayan; Julianto, I Nyoman Larry; Mudra, I Wayan (Universitas Serang Raya, 2025)
An Okokan art group named